High-Energy Gain Upconversion in Monolayer Tungsten Disulfide Photodetectors - Wang, Qixing; Zhang, Qi; Zhao, Xiaoxu; Zheng, Yu Jie; Wang, Junyong; Luo, Xin; Dan, Jiadong; Zhu, Rui; Liang, Qijie; Zhang, Lei; Wong, P. K. Johnny; He, Xiaoyue; et al. (Nano letters, 2019)
Photodetectors usually operate in the wavelength range with photon energy above the bandgap of channel semiconductors so that incident photons can excite electrons from valence band to conduction band to generate photocurrent. Here, however, we show that monolayer WS2 photodetectors can detect photons with energy even lying 219 meV below the bandgap of WS2 at room temperature. With the increase of excitation wavelength from 620 to 680 nm, photoresponsivity varies from 551 to 59 mA/W. This anomalous phenomenon is ascribed to energy upconversion, which is a combination effect of one-photon excitation and multiphonon absorption through an intermediate state created most likely by sulfur divacancy with oxygen adsorption. These findings will arouse research interests on other upconversion optoelectronic devices, photovoltaic devices, for example, of monolayer transition metal dichalcogenides (TMDCs).